ECONOMIC EMPOWERMENT THROUGH ONLINE MARKETS: WOMEN ENTREPRENEURS IN UBERLÂNDIA-MG" - Alberto, Maria Carlos (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
The dynamic transformation of society brought about by technological advancements, particularly the internet and information and communication technologies (ICTs), has ushered in a new era of global connectivity and virtual social interaction. This shift, as identified by Castells (2002), has led to the creation of virtual spaces that transcend physical boundaries, enabling communication on a worldwide scale among individuals, institutions, corporations, and profit-driven entities. This paper explores the expanding digital landscape where human presence and organizational activities extend beyond conventional constraints, as highlighted by Brocklehurst (2001). The integration of these technologies into daily life has reshaped contemporary relationships, exemplified by the growing number of individuals engaging with the internet, particularly through mobile devices and social media platforms. The "Digital 2019" survey, conducted by We Are Social and Hootsuite, underscores this trend in Brazil, revealing that 70% of the population used the internet daily in 2018, with a staggering 94% actively participating in social networks. Among the prominent platforms, such as Youtube, Facebook, WhatsApp, Instagram, Messenger, and Twitter, Instagram experienced the most substantial growth in advertising reach (Kemp, 2019a, 2019b). In light of these transformative shifts, this study examines the profound implications of ICTs on societal structures, communication dynamics, and the nature of human interaction in an increasingly interconnected world.